Detection of Ichthyophthirius multifiliis (Ichthyophthiriidae) in two wild amphibian species - Poonlaphdecha, Srisupaph; Martínez-Silvestre, Albert; Conde, Norma Collado; Ricart, Joan Budó; Suwannarat, Nannaphat; Ribas, Alexis (Frontiers in Veterinary Science, 2025)
Emerging infectious diseases are one of the main threats to global amphibian populations. Frogs and salamanders are already affected by various pathogens, including ranaviruses, Batrachochytrium dendrobatidis, B. salamandrivorans, and helminths. Here, we report the first confirmed cases of Ichthyophthirius multifiliis, a ciliate parasite traditionally considered fish-specific, infecting wild amphibian larvae in a natural setting. As part of a passive surveillance program in Catalonia, five dead amphibians (four S. salamandra larvae and one Rana temporaria post-metamorph) were collected from a freshwater spring and examined for common pathogens. All individuals tested negative for chytrid fungi and ranaviruses by qPCR. However, histological examination of gill tissue revealed the presence of I. multifiliis trophonts in three of the salamander metamorphs and in the frog post-metamorph. In addition, larvae of forty-two amphibians from other localities in Catalonia tested negative. The observed trophonts matched morphological features previously described in teleost infections, including their characteristic macronucleus and surface ciliation. Our results further validate the previous molecular detections and experimental evidence suggesting the parasite’s potential for cross-taxon infection, raising concerns about the overlooked potential prevalence of I. multifiliis in wild amphibians. Given the increasing impact of climate change and habitat alteration on global freshwater ecosystems, this study highlights the importance of including I. multifiliis in amphibian disease monitoring programs.